Island Nasolabial Flap - Bhattacharya, S.; Jaiswal, M.S.D.; Misra, N.C. (Indian Journal of Plastic Surgery, 1990)
The island nasolabial flap was used for the reconstruction of buccal and alar defects in 10 patients. Alar defects produced after ablating small basal cell carcinomas were covered by superiorly based island nasolabial flap and buccal defects caused by incising oral submucous fibrosis and defects following excision of verrucous carcinoma were reconstructed by inferiorly based island nasolabial flap. The incorporation of the underlying vessel in the flap and selective defattening of the flap and it's pedicle by microdissection greatly aids in increasing it's arc of rotation and improving it's maneuverability.
Keywords: Flaps; Nasolabial; Island